A EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR SISWA MTS MATERI KESEBANGUNAN BANGUN DATAR - Cahya Mar’a Saliha Sumantri; Putri, Sulastri Amelia (Center of Education Journal (CEJou), 2023)
Mathematics should be an interesting and enjoyable subject for students. However, for most students, mathematics is a subject that is considered the most difficult, most boring, and often considered the most frightening. This situation causes mathematics to become unpopular and even neglected. Based on these problems or phenomena, it is necessary to implement a learning system that actively involves students in the teaching and learning process to improve mathematics learning at all levels of education. One learning model that involves students actively is the cooperative learning model. The approach used in this study is a quantitative approach, in which the research design is an experimental research type. The experiment referred to in this study is a pure experiment or also known as a true experiment. Data analysis begins with analyzing whether each sample comes from a normally distributed population or not. The results of the normality test with the help of SPSS.22 software show that the sample comes from a normally distributed population because the significance value is greater than the α value. which is homogeneous with a significance value greater than the value of α. The next step is hypothesis testing. Based on the description above, the authors conclude that the experimental class is better than the control class, both in the number of class average scores and in the level of learning completeness. This shows that the application of the Numbered Head Together (NHT) cooperative learning model is "effective" to improve student learning outcomes